Two New Bio-active Flavones from Grangea maderaspatana (Artemisia maderaspatana) - Madhava Rao, V.; Damu, G.L.V.; Sudhakar, D.; Venkata Rao, C. (Asian Journal of Chemistry, 2010)
Two new 5-deoxyflavones, 6-hydroxy-2',4',5'-trimethoxyflavone (1), 6-hydroxy-3',4',5'-trimethoxyflavone (2) and a known flavone, 7,2',4'- trimethoxyflavone (3) have been isolated from the whole plant of Grangea maderaspatana. The isolated compounds were characterized by various spectral methods like UV, IR, Mass, 1D and 2D NMR including NOESY, COSY, HSQC and HMBC studies. The antioxidant and antifungal screening of the isolated compounds were performed in vitro by superoxide free radical scavenging activity method and agar cup method, respectively.